Cultural Determinants of Community in Giving Breast Milk Complementary Food to Babies in Kotamobagu City - Sitti Nurul Hikma Saleh; Agustin, Agustin; Sudirman, Sudirman (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
In Indonesia, achieving the proportion of timely provision of MP-ASI still needs to improve. Providing nutritious food for children and families is inseparable from the culture of the local community, especially the provision of complementary foods for breastfeeding, but cultural principles often contradict the principles of health. This study aims to ascertain the community's cultural norms regarding administering MP-ASI to infants—the cross-sectional design of this study's quantitative descriptive methodology. The population is 231 people. A sample of 148 people was determined based on the Slovin formula. The questionnaire measurement scale uses a Likert scale approach (1-5). Odds ratio analysis is used to analyze data. The study's findings revealed that most mothers with good knowledge in responding to their culture also had good complementary feeding (98.5%), where the odds ratio obtained was 19.950 with a P value. 0.002, with a Lower Bound value of 2.981 and an Upper Bound of 133.533. A good mother's attitude in responding to its relation to her culture mostly shows the proper complementary feeding (94%), with an odds ratio of 4.762 and a significance level of 0.038, a lower bound of 10.90 and an upper bound of 20,813. The cultural determinants of providing complementary feeding (MP-ASI) are in the mother's knowledge and attitude. The knowledge aspect contributes more than the mother's attitude towards proper complementary feeding practices in the local culture.  Keywords: Behavior, complementary feeding, culture, knowledge